Kierkegaard and ironic liberation in “Endgame” - Popovic, Paul (Tropelías: Review of Literary Theory and Comparative Literature, 2003)
Clove’s evasion in Samuel Beckett’s Endgame is presented with a number of strategies that reflect the structure of “ironic liberation” that Kierkegaard puts forward in The concept of irony, with constant reference to Socrates. A variety of objects and ruses guide Clove’s efforts and at the same time divide them into two stages: the cancellation of the dramatic reality and the entrance into the euphoric state. Both stages are marked with changes in protagonist’s behavior and the use of stage elements; and thus, they separate into and interrelate the concrete and abstract components of Endgame’s representation.